The one that moves... doesn’t appear in the photo (Journal of Parents and Teachers, 2023)
The problems at the school are becoming more complex as students grow. Added to this, there is a crisis with the authority figures, which raises the issue of being more stricted or continue giving them freedom.
Keywords: conflicts; free; authority; education